Learning Pattern of Inheritance Tradition of Sustainable Architecture: From Ethno-Architecture to Ethno-Pedagogy - Barliana, M Syaom; Permanasari, Diah Cahyani (TAWARIKH, 2014)
ABSTRACT: Sustainable architecture is not just a matter of technology-related material, the energy use efficiency, land use efficiency, material use efficiency, the use of technology and new materials, and waste management, but also about cultural attitudes and education. In traditional societies, for example, sustainability is happening not only by artefact form, but rather on a belief in the values underlying the respect and understanding to keep the harmony of nature. Therefore, this study wants to focus on two things. Firstly, describing how the behavior patterns of traditional village culture in interacting with the natural environment and the built environment (architecture) in harmony and sustainable. Secondly, examining how patterns of behavior are maintained and passed through a learning process to the next generation. The ethno-architecture and ethno-pedagogy research will use qualitative research methods, which not only focuses on the process (behavior) but also on artefacts as cultural architecture products. The research focus on ethno-architecture shows that the landscape setting of Ciptagelar cultural village in Sukabumi, West Java, Indonesia is generally fit to the sustainable architecture parameters. Meanwhile, ethno-pedagogy sides shows that the tales, advices, poems and childrenâs songs, myths, symbolisms, and belief are some learning pattern of tradition inheritance which content has an effort to live in a harmony with the nature, environment knowledge, environment awareness, and the implementation of environment conservation.KEY WORDS: Ethno-architecture, ethno-pedagogy, Ciptagelar cultural village, sustainable architecture, and the traditions inheritance learning.Â Â About the Authors: Prof. Dr. M. Syaom Barliana and Dr. Diah Cahyani Permanasari are Lecturers at the Department of Architecture Education, Faculty of Vocational Technology Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.207, Bandung 40154, West Java, Indonesia. For academic purposes, the authors can be contacted via their e-mails at: aombarli@yahoo.com and nin_noek252@yahoo.comHow to cite this article? Barliana, M. Syaom & Diah Cahyani Permanasari. (2014). âLearning Pattern of Inheritance Tradition of Sustainable Architecture: From Ethno-Architecture to Ethno-Pedagogyâ in TAWARIKH: International Journal for Historical Studies, Vol.5(2) April, pp.209-222. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (February 23, 2014); Revised (March 27, 2014); and Published (April 28, 2014).